POTENSI GEL HANDSANITIZER EKSTRAK DAUN KITOLOD (Isotoma longiflora L.) SEBAGAI ANTIBAKTERI TERHADAP BAKTERI Staphylococcus aureus - Septiana Laksmi Ramayani (Jurnal Jamu Kusuma, 2022)
Staphylococcus aureus is a Gram positive and commensal bacteria that colonizes 30% of healthy individuals in various parts of the body. Kitolod (Isotoma longiflora L )leaf extract has antibacterial activity against Staphylococcus aureus bacteria and may be developed into hand sanitizer gel preparations. The purpose of this study was to determine the antibacterial activity of the hand sanitizer gel preparation of kitolod leaf extract. Kitolod leaf extract was macerated with 96% ethanol and then formulated into a hand sanitizer gel preparation. Antibacterial activity was carried out using the Kirby Bauer method using a negative control of 10% DMSO and a gel base, while the positive control was a gel hand sanitizer on the market. The results showed that the negative control did not show antibacterial activity, while the positive control, kitolod leaf extract and hand sanitizer gel preparations of kitolod leaf extract gave a clear zone indicating the presence of antibacterial activity against Staphylococcus aureus bacteria. The antibacterial activity of the kitolod leaf extract hand sanitizer gel was classified in the strong category